Coloration enhancement in Procambarus clarkii crayfish through dietary supplementation of phycocyanin extracted from Arthrospira platensis BUUC1503 - Pisan Yodngam; Rachanimuk Hiransuchalert (Veterinary World)
Background and Aim: The effects of phycocyanin (PC) on pigmentation have been extensively studied in fish; however, its specific impact on crustaceans, particularly Procambarus clarkii, remains underexplored. This study aimed to evaluate the impact of PCs extracted from Arthrospira platensis BUUC1503 on the color enhancement of P. clarkii crayfish when added to food pellets.